The Contribution of Residential Planning to Enhance the Sustainability of a High Density City: The Case of Hong Kong (Journal of Bangladesh Institute of Planners, 2014)
Residential planning policy influences the spatial distribution of population and associated facilities and the living environment of the people. The planning of residential area in general and housing as a core component in particular contribute towards the local and global sustainability. Since housing is a key constituent of the built environment and itself is multi-faceted in nature exerting impacts on economic, environmental, social and cultural aspects, its development has to be sustainable in the fullest sense of the word if cities intend to strive for sustainable development. In the high density cities, careful attention is needed for residential planning since more people and activities compete for the scarce land resources in such cities. Hong Kong is well known for its high-density and highrise developments. The paper aims to investigate the contribution of residential planning in enhancing sustainability of Hong Kong as a high density city. At the beginning of the paper, the growth pattern and residential planning of Hong Kong is described in a brief. Then the concept of sustainability and incorporation of the concept in Hong Kong development are discussed. At last, the role of residential planning in enhancing the sustainability of Hong Kong has been critically evaluated. The paper argues that although the principles of residential planning of Hong Kong are contributing to environmental sustainability of the city, the social sustainability has received least attention.Journal of Bangladesh Institute of Planners, Vol. 7, Dec 2014, pp. 33-42